Analysis of Patient Handling Risk Factors for Musculoskeletal Disorders in Care Givers at Adam Malik Haji Center Hospital Medan in 2022 - Dahlia Purba; Sontina Saragih; Jesmo Aldoran Purba (PT Inovasi Pratama Internasional, 2022)
Musculoskeletal disorders are a complaints that are often encountered in every worker. Well that worker offices as well as employees at home sick. According to observations and data obtained, that is complaint about disturbance musculoskeletal to the workers this often occurs in the area of the waist, legs, hands until back. The same is true for nurses who work at home sick. Disturbance musculoskeletal this often occur for nurses and workers alike house sick. because that many conducted study for overcome as well as identify reason as well as risk from disturbance this. From research this obtained that factor profession be one the potential to cause work related musculoskeletal disorders to nurses and assistants nurse at home Adam Malik Hajj Center Hospital Medan. Position anatomy body be one cause for nurses have potency to use get work-related musculoskeletal disorders.